Use of virtual reality for automated driving simulation - Tanjida Tahmina; Mark Fuchs; Chao Shi (Journal of Intelligent and Connected Vehicles)
This study scrutinizes the use of virtual reality (VR) in automated driving simulation environments, with a focus on publication year, driving simulator type, virtual reality (VR) technology, and the advantages and drawbacks of VR application in autonomous driving simulations. An analysis of 87 articles from 10 databases reveals a notable uptick in VR-related research for autonomous driving simulations after 2015, demonstrating VR’s potential in crafting realistic and secure environments for driving research. The identified challenges include motion sickness in participants, validation of driving scenarios, and simulator discomfort, alongside other obstacles and benefits. This study delineates existing research gaps and proposes research directions, aiming to inform and guide subsequent scholarly work at the intersection of VR and autonomous driving research.